Evaluasi Kesiapan Guru P3K dalam Menyelenggarakan Asesmen Diagnostik pada Konteks Kurikulum Merdeka di Daerah Ngapak - Rahayu S, Putri; Setiyadi, Desi; Rohyana, Hadi (FKIP Universitas Wisnuwardhana, 2024)
The Merdeka Curriculum is the main focus of Indonesia's education reform, which introduces a new paradigm for inclusive and adaptive learning. This study evaluates the readiness of P3K teachers in implementing diagnostic assessments in the context of the Merdeka Curriculum, focusing on teachers' understanding, attitudes, and skills and the factors that influence them. Through a qualitative case study approach, results show that some teachers have a good understanding of Merdeka Curriculum and are able to integrate diagnostic assessments effectively, while others need additional assistance. There was variation in the implementation of diagnostic assessments, with some teachers using a more effective holistic approach. Teachers' technical skills also influence the implementation of diagnostic assessments, with some requiring additional training. Continued support from education institutions and local governments is needed to improve teachers' readiness to face the challenges of implementing Curriculum Merdeka and diagnostic assessments. This research provides valuable insights to improve educational practices and ensure more adaptive and relevant learning for students.